The Safety Profile of Vedolizumab in Ulcerative Colitis and Crohn's Disease: 4 Years of Global Post-marketing Data. (13th August 2019) - Cohen, Russell D; Bhayat, Fatima; Blake, Aimee; Travis, Simon
Abstract: Background and Aims: Vedolizumab is a gut-selective antibody to α  4   β  7 integrin, approved to treat moderate-to-severe ulcerative colitis and Crohn's disease in adults. Clinical trial data on patients meeting protocol-specified criteria may not reflect real-world clinical practice. This is a descriptive analysis of 4 years of post-marketing safety data on vedolizumab. Methods: The Vedolizumab Global Safety Database contains all adverse event reports collated by Takeda Pharmaceutical Company Ltd since vedolizumab approval [May 20, 2014]. Adverse event reports received between approval and May 19, 2018 were identified using Medical Dictionary for Regulatory Activities version 21.0 Preferred Terms. Adverse event frequencies were calculated and categorised. Results: In approximately 208 050 patient-years of vedolizumab exposure, 32 752 patients reported 80 218 events. In patients with Crohn's disease or ulcerative colitis, 37 662 and 34 259 events occurred in 14 191 and 14 042 patients, respectively, and 8297 events occurred in 4519 individuals with other [off-label] or unreported indications. Overall, 5230 [14%; Crohn's disease] and 3580 [10%; ulcerative colitis] events were serious. Most frequently reported were gastrointestinal events (Crohn's disease, 6156 [16%]; ulcerative colitis, 5701 [17%]). Patients with Crohn's disease or ulcerative colitis reported 251 malignancies [<1%], 402 hepatobiliary events [<1%], and 5876 infections (1137 serious [19%], 301 opportunistic [5%]). Patients aged ≥70 years [2326 patients] reported <10% of events. Conclusions: Adverse event patterns were consistent with clinical trials, with no new safety concerns. Most reported events were non-serious and event frequency was low, considering patient-years of exposure. Although limitations of post-marketing safety reports require acknowledgement, these real-world data support a favourable safety profile of vedolizumab.